1996
DOI: 10.1007/bf00353944
|View full text |Cite
|
Sign up to set email alerts
|

Large scale production of recombinant mouse and rat growth hormone by fed-batch GS-NSO cell cultures

Abstract: Investigations of biological effects of prolonged elevation of growth hormone in animals such as mice and rats require large amounts of mouse and rat growth hormone (GH) materials. As an alternative to scarce and expensive pituitary derived materials, both mouse and rat GH were expressed in NSO murine myeloma cells transfected with a vector containing the glutamine synthetase (GS) gene and two copies of mouse or rat GH cDNA. For optimal expression, the mouse GH vector also contained sequences for targeting int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…This occurs even when there is considerable glucose remaining in the culture medium. Only with pH shifts above pH 8.0 did lactate continue to accumulate in the medium after 48 h. This has also been observed by Zhou et al (1996Zhou et al ( , 1997 who investigated nutrient-feeding strategies for batch culturing of a similar GS-NS0 cell line. They reported a similar shift in lactate metabolism from production to consumption and postulated that this switch occurred when the cells became pyruvate limited; lactate being consumed to supply pyruvate.…”
Section: Cell Metabolism After Ph Shiftsmentioning
confidence: 61%
See 1 more Smart Citation
“…This occurs even when there is considerable glucose remaining in the culture medium. Only with pH shifts above pH 8.0 did lactate continue to accumulate in the medium after 48 h. This has also been observed by Zhou et al (1996Zhou et al ( , 1997 who investigated nutrient-feeding strategies for batch culturing of a similar GS-NS0 cell line. They reported a similar shift in lactate metabolism from production to consumption and postulated that this switch occurred when the cells became pyruvate limited; lactate being consumed to supply pyruvate.…”
Section: Cell Metabolism After Ph Shiftsmentioning
confidence: 61%
“…Although these changes were kept to a minimum, the calculated pCO 2 values decreased from 146 mm Hg at pH 6.5 to 2 mm Hg at pH 9.0 and the calculated bicarbonate concentration increased from 1.13 g/L at pH 6.5 to 4.17 g/L at pH 9.0. Generally, data concerning the independent effect of pCO 2 on GS-NS0 cells is scarce, although Zhou et al (1996) and Aunins and Hensler (1993) reported that an increase in pCO 2 to 120 mm Hg accompanied by increasing osmolarity did not affect the culture performance of a similar GS-NS0 cell line. In addition, Kimura and Miller (1996) have investigated the effect of pCO 2 on CHO cells.…”
Section: Resultsmentioning
confidence: 96%
“…Increased productivity has also been realized through intensive bioprocess engineering research. The employment of fedbatch culture ( (Bibila et al, 1994;Bibila and Robinson, 1995;Xie and Wang, 1996;Zhou et al, 1996Zhou et al, , 1997a, reviewed in (Wlaschin and Hu, 2006)) has been instrumental in In recent years, both transcriptome and proteome analytical tools have gained popularity in cell culture applications, as reviewed in Gupta and Lee (2007). These applications have included the study of cell lines of varying productivities (Khoo et al, 2007;Seth et al, 2007a,b), as well as different culture conditions known to impact recombinant protein production (Baik et al, 2006;Shen and Sharfstein, 2006;De Leon Gatti et al, 2007;Yee et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 95%
“…Correspondence to: J.-D. Yang for large-scale antibody production using this fed-batch approach (Bibila and Robinson, 1995;Seaver, 1997;Zhou et al, 1996Zhou et al, , 1997b.…”
Section: Introductionmentioning
confidence: 99%